Challenges for cultural relevance of physical therapy in the care of the Mapuche population in Chile - Mónica Manríquez-Hizaut; Trinidad Martínez-Campos; Nicolás Lagos-Gallardo; Jame Rebolledo-Sanhueza (Salud Colectiva)
Physical therapy rehabilitation must address the cultural preferences of the population, and as its main tool, physical activity should be analyzed from an intercultural health approach. This study aims to characterize the experiences of physical therapy care related to physical activity from an intercultural perspective. Using a qualitative approach, between June 2021 and March 2023, eight semi-structured individual interviews were conducted with adult Mapuche individuals, professionals in the field, and workers from the Indigenous Health Program in primary care centers in an urban municipality in Santiago, Chile. There are challenges to implementing interculturality, such as the gap between health programs, lack of professional training, and discrimination against the Mapuche community. In rehabilitation services, particularly in physical activity practices as a treatment strategy for Mapuche individuals, cultural relevance is limited or nonexistent.